2010
DOI: 10.1371/journal.pone.0009183
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine-Associated Early Hepatotoxicity: Incidence, Risk Factors, and Associated Mortality in a Primary Care ART Programme in South Africa

Abstract: BackgroundThe majority of antiretroviral treatment programmes in sub-Saharan Africa are scaling up antiretroviral treatment using a fixed dose first-line antiretroviral regimen containing stavudine, lamivudine, and nevirapine. One of the primary concerns with the use of this regimen is nevirapine-associated hepatotoxicity.Methodology/Principal FindingsStudy participants were 1809 HIV-infected, antiretroviral naïve adults initiating nevirapine-based antiretroviral therapy between November 2002 and December 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
3
27
0
1
Order By: Relevance
“…This is probably because the courses of HIV pathogenesis and drug metabolism in humans generally are not sex dependent. This finding is similar with the findings of previous studies carried out in different countries such as Nigeria (6), Cameron (20), South Africa (21), Swiss (22) and Brazil (23). As found out in this study, age difference is not also a determinant factor for liver enzyme elevations.…”
Section: Discussionsupporting
confidence: 92%
“…This is probably because the courses of HIV pathogenesis and drug metabolism in humans generally are not sex dependent. This finding is similar with the findings of previous studies carried out in different countries such as Nigeria (6), Cameron (20), South Africa (21), Swiss (22) and Brazil (23). As found out in this study, age difference is not also a determinant factor for liver enzyme elevations.…”
Section: Discussionsupporting
confidence: 92%
“…Hypersensitivity reactions and increases in hepatic transaminases are among the most common toxicities associated with nevirapine use. The results of several studies of the safety profile of nevirapine indicate that 2 to 13% of patients receiving this drug develop hepatotoxicity symptoms and that this risk increases in the presence of coinfections such as hepatitis B or C (Sulkowski et al, 2002;Ena et al, 2003;Stern et al, 2003;van Leth et al, 2004;Chu et al, 2010). In general, hepatitis secondary to nevirapine occurs at approximately 12 weeks after the initiation of treatment and is often accompanied by a skin rash.…”
Section: G Atp-binding Cassette Subfamily B Member 1 Transporter (P-mentioning
confidence: 99%
“…The observations in TDF/NVP treated rats suggest signs of oxidative hepatorenal damage (Adaramoye et al, 2012).This could be attributed to oxidative stress induced by these agents in the kidney and liver of treated rats via the generation of oxidative radicals which might have led to the depletion of these antioxidants (Ramamoorthy et al, 2008). In the present study, observed depletion in kidney antioxidants could be attributed to the toxic effect of tenofovir on the kidneys of treated rats (Martínez et al, 2001) while decreases in antioxidant levels in the liver of TDF/NVP treated rats could be attributed to the toxic effect of nevirapine on the liver (Chu et al, 2010;Adikwu and Brambaifa, 2013) Reduced glutathione (GSH) is the most prevalent non-protein thiol in animal cells. It is involved in the detoxification of a variety of electrophilic compounds and peroxides via catalysis by glutathione S-transferase (GST) and glutathione peroxidases (GPx) (Anderson, 1998;Mullineaux, and Creissen, 1997;Babiak., et al, 1998).…”
Section: Resultsmentioning
confidence: 55%